Management of Idiopathic Gingival Fibromatosis in a Child with Autism: A Case Report (Journal of Dentistry and Allied Science, 2025)
Gingival fibromatosis is a rare disorder characterized by abnormal enlargement of gingival tissue. It is usually associated with systemic conditions, different syndromes, genetic conditions, drug induced or might be idiopathic in origin. It is slow progressive in nature and mostly occurs during the stages of tooth eruption. The condition give rise to different problems such as pain, delayed eruption, masticatory pain, periodontal disease, dental caries and aesthetic concern. The oral hygiene status of patient has an important role on further deterioration of the condition. The treatment option varying from simple management by oral hygiene instruction to surgical approach, depends on the severity of the lesion. This case report describes clinical manifestations and management of a case of idiopathic gingival fibromatosis in an eleven years old autistic child. In this case, the classical manifestations of gingival fibromatosis were encountered and was managed by surgical excision under general anesthesiaJournal of Dentistry and Allied Science, Vol. 8 No 1: 53-57